Customer Acquisition Strategy in Procurement Business (Case Study of CV SAS) - Firdausya, Asty; Windasari, Nila Armelia (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2025)
The procurement industry is currently growing, this situation is driven by its vital role in business operations and spending decisions. This growth has created opportunities and intensified competition. CV SAS is one company that sees business opportunities in the procurement industry. CV SAS has established a sustainable business with reputable buyers, increasing revenue, and 18 procurement licenses across various industries. However, its reliance on a single customer poses significant risks, including dependency and limited diversification. To address this, CV SAS must focus on acquiring new customers to reduce risks, improve bargaining power, diversify revenue streams, and achieve stable growth. The company plans to use strategies like SWOT analysis and market segmentation internally, while also applying external tools like Porter’s Five Forces and buyer behavior analysis to understand and target potential customers effectively.